Deficit of digital orientation among service-based firms in an emerging economy: a resource-based view - John Amoah; Abdul Bashiru Jibril; Michael Amponsah Odei; Sulemana Bankuoru Egala; Raymond Dziwornu; Kofi Kwarteng (Cogent Business & Management, 2023)
AbstractDigital technologies are essential tools that Service-based firms can integrate into their business to transform their operations. However, in the emerging countries’ perspective, research on the application of digital orientation among Service-based firms is less researched. This poses questions to scholars why the adoption of digital orientation is quite low among developing economies. The purpose of this article is to examine the impediments to digital orientation among Service-based firms in emerging and developing countries. Inspired by a resource-based view, a survey using a structured questionnaire was administered to 466 respondents (management and employees) of Service-based firms via a convenience sampling method in Ghana. Findings revealed that the knowledge gap, cost burden, and upgrading of technology positively and significantly create the gap in digital orientation among Service-based firms. The authors admonished that Service-based firms should 'be orient' on the use of digital technologies through appropriate training programs to enhance its adoption. The study again recommends practitioners of Service-based firms cultivate the habit of investing in human and technical capacities to optimize the benefits of the evolution of digital technologies. Limitations and future research directions are discussed.